DUNIA PEREMPUAN DALAM KARYA SASTRA PEREMPUAN INDONESIA (Kajian Feminisme) - Hayati, Yenni (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This article describes the world of and images of women depicted in women fiction writer, particularly in short story literature. In depicting women’s world, an Indonesian writer tends to focus on their domestic than public life. This is because domestic life is considered safer for women, and women are considered best settled in the domestic life. There are six images closely associated with women; a mother, a loyal woman, a successful woman, a second woman, an ideal woman, and a bad woman. Mother image is the most found, 14 of 15 fictions examined in this research. The description of domestic life associates with mother image, because the two are closely related with the life of Indonesian women. Key words: women’s world, women’s image, women’s literature